Odpowiedzi

  • Grel
  • Początkujący
2009-11-29T17:33:46+01:00
Jeżeli to układ równań to:
3x-2y=4
3x-y=5 | *(-1)

3x-2y=4
-3x+y=-5
-------------
-y = -1 | * -1
y=1

3x-2 * 1 = 4
3x -2 = 4
3x = 6
x = 2



Rozwiązaniem tych układow równań są liczby y= 1 i x= 2
1 5 1
Najlepsza Odpowiedź!
2009-11-29T17:35:12+01:00
3x-y=5
-y=-3x+5
y=3x-5


3x-2y=4
3x-2(3x-5)=4
3x-6x+10=4
-3x=-6
x=2


y=3x-5
y=3*2-5
y=1



x=2
y=1
2 5 2
2009-11-29T17:37:43+01:00
3X-2Y=4
3x-y=5|x(-2)

3X-2Y=4
-6x+2y=-10
_________
-3x=-6|:-3
x=2

y=3x-5
y=6-5
y=1






1 5 1